2015
DOI: 10.1002/hyp.10731
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous drip in the Punkva caves (Moravian Karst): relevant implications for paleoclimatic proxies

Abstract: Abstract:The anomalous drip in the Punkva caves (Moravian Karst) shows specific hydrogeochemical properties such as low SI calcite~0 .14 ± 0.11 (standard deviation), low mineralization (4.53 ± 0.42) × 10 À3 mol l À1, and enhanced values of δ 13 C (À7.85 to À8.35‰ VPDB), Mg/Ca × 1000 ratio (45.7 ± 3.3), and Sr/Ca × 1000 ratio (0.65 ± 0.06). By these properties, the anomalous drip significantly differs from other regular drips in the same cave and other caves in the region. The study suggests that the anomalous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…From a visual inspection of the ceiling, we concluded that precipitation does not readily occur at the ceiling. However, PCP could be important, as many of the geochemical parameters resulting from this process were found in our data (low SEC, low SI cc and low mineralisation [27,57]). However, to diagnose PCP, at least the ratios of the trace elements (e.g., Mg/Ca and Sr/Ca) and the δ 13 C signature would need to be determined, with higher values being a key signal for this process.…”
Section: Dripwater Entering the Cave Atmospherementioning
confidence: 54%
See 1 more Smart Citation
“…From a visual inspection of the ceiling, we concluded that precipitation does not readily occur at the ceiling. However, PCP could be important, as many of the geochemical parameters resulting from this process were found in our data (low SEC, low SI cc and low mineralisation [27,57]). However, to diagnose PCP, at least the ratios of the trace elements (e.g., Mg/Ca and Sr/Ca) and the δ 13 C signature would need to be determined, with higher values being a key signal for this process.…”
Section: Dripwater Entering the Cave Atmospherementioning
confidence: 54%
“…However, to diagnose PCP, at least the ratios of the trace elements (e.g., Mg/Ca and Sr/Ca) and the δ 13 C signature would need to be determined, with higher values being a key signal for this process. Alternatively, mixing corrosion could provide a source of potential dissolution in the Red Hall [57]. However, both mixing corrosion and PCP in the vadose zone are highly unlikely to control the geochemistry in our case, as there is simply an abundance of corrosion features over a wide area fed by several hundred different drips.…”
Section: Dripwater Entering the Cave Atmospherementioning
confidence: 92%
“…From visual inspection of the ceiling, we concluded that precipitation does not readily occur at the ceiling. However, PCP could be important as many of the geochemical parameters resulting from this process are found in our data (low SEC, low SIcc and low mineralisation; [58]). However, to diagnose PCP, at least the ratios of trace elements (e.g.…”
Section: Dripwater Entering the Cave Atmospherementioning
confidence: 61%
“…Mg/Ca and Sr/Ca) and the δ 13 C signature would need to be determined, with higher values being a key signal for this process. Mixing corrosion as a source of potential dissolution in the Red Hall might also play a role [58], but this scenario, as well as PCP that would have to take place in the vadose zone, are highly unlikely to control the geochemistry in our case, as there is simply an abundance of corrosion features over a wider area fed by several hundred different drips.…”
Section: Dripwater Entering the Cave Atmospherementioning
confidence: 94%